Dari Perencanaan hingga Asesmen: Implementasi Kurikulum Merdeka dalam Pembelajaran Sejarah di SMAN 1 Sikur Lombok Timur - Baiq Silviana Artika; B. Fitri Rahmawati; Zidni Zidni (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
The implementation of the Merdeka Curriculum requires changes in the planning, enactment, and assessment of history learning. This study aims to analyze its implementation at SMAN 1 Sikur by examining these three dimensions. A descriptive qualitative approach was employed. Data were collected through observation, structured interviews with the principal, a history teacher, and four students, as well as documentation of learning outcomes, learning objectives, learning objective sequences, teaching modules, and assessment instruments. Data were analyzed through reduction, display, and conclusion drawing. The findings show that the school prepared implementation through in-house training, workshops, and a learning community. The teacher had developed learning outcomes, objectives, objective sequences, and teaching modules, and had sought to adapt learning to students’ interests, needs, and characteristics. Differentiation was evident in learning processes and products, yet it was not consistently implemented because of student heterogeneity and classroom-management constraints. Diagnostic, formative, and summative assessments were applied, although time management remained problematic. The curriculum has therefore been implemented substantively in history learning at SMAN 1 Sikur, but further strengthening is needed in teacher competence, operational differentiation design, and effective assessment management.